Akhlak Guru Terhadap Murid Dalam Proses Pendidikan di Era Milenial Perspektif Imam Ghazali - Muhamad Akip (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2020)
This study aims to describe and analyze the morals of teachers towards students in the educational process in the millennial era, the perspective of the ghazali imam in the book Ihya 'Ulumuddin, teachers are a noble profession so that people who become teachers are emulated by each student and teachers must have ethics towards their students (1) Shows the nature of affection for students. and treat him like his own son. (2) The teacher must carry out what has been conveyed to the student. (3) Teachers are not allowed to ask for favors or compensation from students (4) Giving knowledge systematically (5) Teachers are not allowed to rebuke their students (6) A teacher is responsible for one of the subjects. (7) The teacher must explain the lesson according to the understanding of the student. (8) Students who are slow in understanding lessons, should be given clear lessons or (remedial) so that patiently they will receive blessings and ta'zim their teachers. The concept of education put forward by Imam Ghozali is still very relevant to the laws that apply in this millennial era and serves as a bridge between the concept of Imam Ghozali and the Law which in the application process is not in accordance with the concept or law because of the moral position above science and knowledge. the average knowledgeable person can be seen from the morals of both fellow humans and other God's creations.